Research on Teaching Economics to Undergraduates - Allgood, Sam; Walstad, William B.; Siegfried, John J. (Journal of Economic Literature, 2015)
This survey summarizes the main research findings about teaching economics to undergraduates. After briefly reviewing the history of research on undergraduate economic education, it discusses the status of the economics major—numbers and trends, goals, coursework, outcomes, and the principles courses. Some economic theory is used to explain the likely effects of pedagogical decisions of faculty and the learning choices that students make. Major results from empirical research are reviewed from the professor perspective on such topics as teaching methods, online technology, class size, and textbooks. Studies of student learning are discussed in relation to study time, grades, attendance, math aptitude, and cheating. The last section discusses changes in the composition of faculty who teach undergraduate economics and effects from changes in instructional technology and then presents findings from the research about measuring teaching effectiveness and the value of teacher training. (JEL A22, I23, J44)